Transformasi Pendidikan Perempuan Melalui Hukum Islam Pendekatan Integratif Berbasis Nilai Islami - Halim, Abdul; Fatoni, Imam (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
Education in Islam emphasises gender equality, which is reflected in the obligation to pursue knowledge for every individual regardless of gender. qualitative approach with literature study design (library research) The results of the study are: The application of Islamic values in women's education has an important role in improving access and quality of education without gender discrimination. Islam teaches equality, justice and responsibility, which can open wider opportunities for women to develop knowledge as well as moral and spiritual character. By instilling values such as trustworthiness and responsibility, women are expected to contribute more to society and reduce the gender gap. Therefore, collaboration between the government, educational institutions and society is essential to create an inclusive education system that supports women's empowerment, so that women can play a vital role in building civilisation and achieving a more just and prosperous future.